Disparities in Forensic Science Adoption for Crime Investigation in Kenya: The Role of Police Demographics - Miano, Dennis; Anangwe, K.; Kiemo, K. (SAGE open, 2024)
Widespread disparities in the adoption of forensic science (FS) in criminal investigations remain a global issue. Although multiple factors have been identified to cause disparities in the adoption of forensic science, little consideration has been given to the socio-demographic characteristics of police officers in explaining these disparities. This study analyzes police demographic characteristics using a cross-sectional descriptive survey of 146 Directorate of Criminal Investigation (DCI) officers in Kenya in relation to the adoption of FS in crime investigation. A binary logistic regression was performed to assess the predictive value of each demographic characteristic, including gender, level of education, police experience, police rank, favorite subject (science or non-science) in high school, and service formation, on the adoption of FS. We found that the composite police demographic variable was not statistically significant (p = .877) in predicting the adoption of FS in crime investigations. Officers with higher levels of education (bachelor’s degree) and mid-level service experience showed significantly (p < .05) higher odds of adoption of FS. All other demographic variables (gender, service ranks, and service formation) were not statistically significant in predicting the adoption of FS. In conclusion, the disparities in the adoption of FS can be traced back to police demographic characteristics, particularly different levels of education, and experience among officers. We recommend police departments rethink the combined effect of police demographic characteristics in a bid to reduce disparities in the adoption of FS in crime investigations. Plain Language Summary This study sought to analyze police demographic characteristics using a cross-sectional descriptive survey of 146 Directorate of Criminal Investigation (DCI) officers in Kenya in relation to the adoption of FS in crime investigation. A binary logistic regression was performed to assess the predictive value of each demographic characteristic, including gender, level of education, police experience, police rank, favorite subject (science or non-science) in high school, and service formation, on the adoption of FS. We found that the composite police demographic variable was not statistically significant (p = .877) in predicting the adoption of FS in crime investigations. Officers with higher levels of education (bachelor degree) and mid-level service experience showed significantly (p <.05) higher odds of adoption of FS. All other demographic variables (gender, service ranks, and service formation) were not significant in predicting the adoption of FS but showed a correlation. In conclusion, the disparities in the adoption of FS can be traced back to police demographic characteristics, particularly different levels of education and experience among officers. The study result imply that police departments need to rethink the combined effect of police demographic characteristics in a bid to reduce disparities in the adoption of FS in crime investigations. The study dependent variable is limited in the sense that, there is need to enhance clarity on the construct of FS, and use of a specific crime or scenario based approach in determining intention to adopt forensic science